2019
DOI: 10.1016/j.disc.2018.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Pretty good quantum state transfer in asymmetric graphs via potential

Abstract: We construct infinite families of graphs in which pretty good state transfer can be induced by adding a potential to the nodes of the graph (i.e. adding a number to a diagonal entry of the adjacency matrix). Indeed, we show that given any graph with a pair of cospectral nodes, a simple modification of the graph, along with a suitable potential, yields pretty good state transfer (i.e. asymptotically perfect state transfer) between the nodes. This generalizes previous work, concerning graphs with an involution, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…However, if we are interested in pretty good state transfer from u to v, that is, for any ǫ > 0, there is a time k at which the probability of being on v is ǫ-close to 1, given initial state e u ⊗ x, then the eigenvalue conditions in Theorem 5.3 can be relaxed. Pretty good state transfer has been found in continuous quantum walks, see for example [5,24,15,17]. We would like to see discrete analogues.…”
Section: Open Problemsmentioning
confidence: 95%
“…However, if we are interested in pretty good state transfer from u to v, that is, for any ǫ > 0, there is a time k at which the probability of being on v is ǫ-close to 1, given initial state e u ⊗ x, then the eigenvalue conditions in Theorem 5.3 can be relaxed. Pretty good state transfer has been found in continuous quantum walks, see for example [5,24,15,17]. We would like to see discrete analogues.…”
Section: Open Problemsmentioning
confidence: 95%
“…is fulfilled for all λ. In words, u and v are cospectral if and only if, within each degenerate subspace, the sum of squares of absolute values of projections on sites u is equal to that of projections on site v. If u and v are cospectral and additionally [11] λ i |u = ± λ i |v…”
Section: Strong Cospectrality and The Impact Of Symmetriesmentioning
confidence: 99%
“…On the other hand, meeting the spectral requirements remains a difficult task. Nevertheless, in a recent paper [11] by Eisenberg et al, this has been rendered simpler for the case of PGST. They showed that Eqs.…”
Section: Designing Graphs Featuring Strongly Cospectral Verticesmentioning
confidence: 99%
See 2 more Smart Citations